Pengaruh Kecenderungan Narsistik dengan Intensitas Penggunaan Media Sosial Tiktok - Eka Wulan Astutik; Nabila Dhita Syaharani; Nafadhilla Refie Anjani; Abdullah Azzam Al Afghani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The rapid advancement of technology, especially in the field of information and communication technology, makes it easier for humans to interact with each other. One of the impacts of the development of information and communication technology is the emergence of digital platforms or social media. In this study, the method used is quantitative method using causality research design. This study concluded that there is no significant influence between narcissistic tendencies and the intensity of TikTok use. This finding contradicts several previous studies that show a positive correlation between the two.